2020
DOI: 10.17932/ejoh.2020.022/ejoh_v02i1003
|View full text |Cite
|
Sign up to set email alerts
|

Metformin-Loaded Nanostructured Plga: A New Strategy for Enhancing Efficacy of Metformin in Breast Cancer Treatment

Abstract: Objective: Nano-formulation approaches would be more efficient in decreasing drug toxicity, preventing tumor development in relation to free form of drug.Methods: Therefore, the purpose of this study is to construct poly lactic-coglycolic acid (PLGA) nanoparticles (NPs) loaded with Metformin (MET) to investigate their cytotoxicity as well as their impact on expression levels of apoptosis related genes in MDA-MB-231 breast cancer cells. Field Emission Scanning Electron Microscope (FE-SEM) and Fourier-transform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…To enhance the efficacy of MET in cancer therapy, researchers have been exploring various combination therapies. For example, a recent study has illustrated that combining MET with nanostructured poly lactic-coglycolic acid (PLGA) can improve its effectiveness in treating breast cancer [164]. Additionally, Han et al have shown that concurrent administration of MET with EGFR-TKIs can lead to better clinical results and delay the onset of EGFR-TKI resistance in non-small cell lung cancer patients.…”
Section: Metformin and Chemotherapy And Limitationsmentioning
confidence: 99%
“…To enhance the efficacy of MET in cancer therapy, researchers have been exploring various combination therapies. For example, a recent study has illustrated that combining MET with nanostructured poly lactic-coglycolic acid (PLGA) can improve its effectiveness in treating breast cancer [164]. Additionally, Han et al have shown that concurrent administration of MET with EGFR-TKIs can lead to better clinical results and delay the onset of EGFR-TKI resistance in non-small cell lung cancer patients.…”
Section: Metformin and Chemotherapy And Limitationsmentioning
confidence: 99%
“…For example, a recent study has illustrated that combining MET with nanostructured poly lactic-coglycolic acid (PLGA) can improve its effectiveness in treating BC. 181 treatments for patients in the future. 184 Additionally, Autophagy is a resistance mechanism that limits the effectiveness of enzalutamide, a small molecule used to treat castrationresistant prostate cancer.…”
Section: Overcome the Limitations Of The Therapeutic Effects Of Metfo...mentioning
confidence: 99%
“…To enhance the efficacy of MET in cancer therapy, researchers have been exploring various combination therapies. For example, a recent study has illustrated that combining MET with nanostructured poly lactic‐coglycolic acid (PLGA) can improve its effectiveness in treating BC 181 . Additionally, Han et al have shown that concurrent administration of MET with EGFR‐TKIs can lead to better clinical results and delay the onset of EGFR‐TKI resistance in non‐small cell lung cancer patients.…”
Section: Overcome the Limitations Of The Therapeutic Effects Of Metfo...mentioning
confidence: 99%